Locus Surfaces and Linear Transformations When Fixed Point Is at Infinity (Research Journal of Mathematics & Technology, 2022)
We extend the locus problems discussed in [9], [10] and [12], for a quadric surface whenthe fixed point is at an infinity. This paper will benefit those students who have backgroundsin Linear Algebra and Multivariable Calculus. As we shall see that the transformationfrom a quadric surface $\sum$ to its locus surface $Δ$ is a linear transformation. Consequently,how the eigenvectors are related to the position of the fixed point at an infinity will bediscussed.